Formulasi Nanosuspensi Herbal Ekstrak Daun Cosmos caudatus Kunth., Karakterisasi, dan Pendekatan Sitotoksisitas Terhadap Sel Kanker Payudara MCF-7 - Nafisa, Safira; Noor, Siti Umrah; Azkannufuus, Azkannufuus; Noviani, Yuslia (JURNAL ILMU KEFARMASIAN INDONESIA, 2023)
Kenikir leaves (Cosmos caudatus Kunth.) contain quercetin, which has anticancer properties. To provide more effective complementary therapy for breast cancer, nanotechnology was applied to develop preparations containing kenikir leaf extract. This research aimed to formulate a nanosuspension containing kenikir leaf extract with cytotoxic activity against MCF-7 breast cancer cells. Nanosuspension of kenikir leaf extract was prepared using the ionic gelation method with 3%, 4%, and 5% PVP K-30 stabilizer. The nanosuspension formula with the highest entrapment efficiency was further characterised, including particle size, polydispersity index (PDI), zeta potential, pH, and particle morphology. Cytotoxic activity was tested against MCF-7 cells by the MTT assay. The results showed that the formula with 5% PVP has the highest entrapment efficiency value of 85.04±0.08%, a particle size of 221.9 nm, a PDI of 0.211, a zeta potential of -21.7 mV, a pH of 4.08±0.0, and a spherical morphology. The kenikir leaf extract at a concentration of 1 mg/mL inhibited the proliferation of MCF-7 cells by 23.4% (p<0.05), whereas the nanosuspension at 10 μg/mL inhibited proliferation by 23.7%. It can be concluded that kenikir leaf extract can be formulated into a nanosuspension that meets the physical criteria and has cytotoxic activity against MCF-7 cells.